(untitled) - Keizo, Shibusawa (Tokyo, 1958)
This book consists of the following many chapters: opening of Japan at the end of the shogunate and its effects; change of social conditions; Transition and development of economic policy; development of the monetary system; development of light industry; development of mining industry; development of transportation and communications system; development of agricultural and marine industries; development of foreign trade.